The Effects of Direct-fed Microbial, Primalac®, or Salinomycin Supplementation on Intestinal Lactate Isomers and Cecal Volatile Fatty Acid Concentrations in Broilers1 - Croom, J.; Chichlowski, M.; Froetschel, M.; McBride, B.W.; Qui, R.; Koci, M.D. (International Journal of Poultry Science, 2009)
Direct-Fed Microbials (DFM) are a putative alternative to the feeding of sub-therapeutic levels of antibiotics in the production of poultry and other livestock species. This study was designed to examine the effects of a commercial DFM (Primalac®), or salinomycin (SAL), a commonly used antibiotic and coccidiostat supplement, on fermentation patterns and lactate production in the cecum and the lower intestinal tract of broiler chickens. L-lactate and total lactate concentrations in the digesta fluid of the ileum decreased (P<0.01) with the DFM feeding in comparison to CON and SAL treatments while d-lactate concentration increased (P<0.04) in comparison to CON. Total cecal VFA concentration was lower (P<0.003) with DFM feeding and SAL than the CON. In the present study both dietary supplements, DFM and SAL, altered lactic acid and VFA concentrations in the cecum and intestines of experimental animals; however the full spectrum of mechanisms responsible for antibacterial properties and growth promotion associated with those changes remains to be elucidated.